Changes in Sexuality of Castration-Resistant Prostate Cancer Patients under Hormone Therapy in Japan: A Case Study - Kashiwagi, Yoshiyuki; Kakinohan, Shige (Nurse Media Journal of Nursing, 2016)
Background: Hormone therapy is an important treatment for male patients with prostate cancer. However, it can produce changes in the genitalia and sexuality of the patients. Purpose: This study aimed to investigate the relations between changes in male genitalia and sexuality in the castration-resistant prostate cancer patients. It also proposed concrete interventions to ease pain and fear towards body image changes. Methods: This study used a descriptive qualitative design. The subjects were two castration-resistant prostate cancer patients undergoing chemotherapy and endocrine therapy. The data were collected through semi-structured interviews and analyzed using verbatim reports and content analysis. Results: The study indicated that the effects of hormone therapy treatment on the sexuality were largely categorized as: â€œsurprises and anxieties about the shrinkage of male genitaliaâ€, â€œmasculinity lossâ€, â€œdifficulty adapting the situationâ€, and â€œconnection with othersâ€. Conclusion: It became clear that the prostate cancer patients had pains not only for prognosis, but also for physical changes, relationship changes with others and sexuality changes through their treatments.